PENGARUH PENAMBAHAN LABU KUNING (Cucurbita moschata) DAN UBI JALAR UNGU (Ipomoea batatas L) TERHADAP KECEPATAN LELEH ES KRIM YANG DIHASILKAN - Nuralizah, Nuralizah; Adam, Asmah; Fadilah, Ratnawaty (Universitas Negeri Makassar, 2016)
This study aimed to determine the effect of pumpkin and purple sweet potato on the physical properties of ice cream and to find acceptance panelists against the ice cream produced. This research method using a complete randomized design (CRD ). The results showed that the observation of the overrun , melting speed and the results organoleptic (color , aroma, taste and texture) obtained the best results in the addition of 15 % is good on ice cream or ice cream pumpkin purple sweet potato